1998
DOI: 10.1152/ajprenal.1998.275.4.f595
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A increases hypoxia and free radical production in rat kidneys: prevention by dietary glycine

Abstract: The major side effect of cyclosporin A is severe nephrotoxicity. It is likely that cyclosporin A causes vasoconstriction leading to hypoxia-reperfusion injury; therefore, these experiments were designed to attempt to obtain physical evidence for hypoxia and free radical production in kidney following cyclosporin A. Rats were treated daily with cyclosporin A (25 mg/kg ig) for 5 days, and pimonidazole, a hypoxia marker, was injected 2 h after the last dose of cyclosporin A. A dose of α-(4-pyridyl-1-oxide)- N- te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(172 citation statements)
references
References 33 publications
12
158
0
2
Order By: Relevance
“…It has previously been suggested that aggravated low oxygen tension in the renal medulla may cause progression of nephropathy [5,6]. In view of our previous [8] and present results with markedly decreased renal tissue oxygen tension during chronic hyperglycaemia, we conducted separate experiments applying microdialysis to assess the regional interstitial metabolic environment in vivo.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has previously been suggested that aggravated low oxygen tension in the renal medulla may cause progression of nephropathy [5,6]. In view of our previous [8] and present results with markedly decreased renal tissue oxygen tension during chronic hyperglycaemia, we conducted separate experiments applying microdialysis to assess the regional interstitial metabolic environment in vivo.…”
Section: Discussionmentioning
confidence: 89%
“…The majority of studies on diabetic nephropathy have been conducted in vitro and/or have focused on glomerular changes. In the kidney, the medullary region is particularly vulnerable to decreased oxygen concentration because of its low blood perfusion and high basal oxygen consumption [5,6]. Even during normal situations, the renal medulla works at the threshold of hypoxia [5,6] and has an oxygen extraction from the blood of about 90% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Steep oxygen gradients would foreshorten the distance over which divergent K m s are traversed, possibly reducing the distance to the two or three cell diameters observed in moderately differentiated tumours ( Figure 4C and D) and in normal tissues such as the liver and kidney (Arteel et al, 1995;Zhong et al, 1998). Conversely, shallow gradients would increase the distance over which divergent K m s are traversed allowing for involucrin induction in advance of pimonidazole binding as appears to be the case in Figure 4A and B.…”
Section: Discussionmentioning
confidence: 91%
“…Surgically induced renal ischaemia has also been shown to accelerate the progression of nephropathy in STZ-diabetic rats [24]. In the kidney, the renal medullary region is particularly vulnerable to decreased tissue oxygen tension because of its low blood perfusion and high basal oxygen consumption [25,26]. Already during normal circumstances, the renal medulla works at the threshold of hypoxia [25,26] and has an oxygen extraction rate of about 90% [27].…”
Section: Discussionmentioning
confidence: 99%